POTENSI ANTIOKSIDAN DALAM KELOPAK BUNGA ROSELLA (Hibiscus sabdariffa L.) SEBAGAI ANTI-AGING - Malinda, Okta; Syakdani, Adi (Politeknik Negeri Sriwijaya, 2020)
Roselle flower (Hibiscus sabdariffa L.) contain compounds that have anioxidan so it can ward off free radicals. The value of roselle benefit is very wide both for food and health, so the potential of roselle diversification is quite large. The important ingredients found in roselle petals are anthocyanin pigments that act as antioxidants. The purpose of this article review is to know the potential of antioxsidan in roselle flowers (Hibiscus Sabdariffa L.) as anti-aging. Review of this article is using comparative research methods from various sources and from various research journals with a minimum number of 25 research journals. The results of this review suggest that the roselle flower (Hibiscus sabdariffa L.) has potential as anti-aging of the leaves, fruits, and petals of the roselle (Hibiscus sabdariffa L.) has been shown to contain antioxidant.